ASSESSMENT OF DENTAL STATUS AND DMFT INDEX IN PREGNANT WOMAN ATTENDING COMMUNITY HEALTH CENTRE MADE, SURABAYA - Amaliah, Nurfitri; Harryadi, Carera Iva; Sanjaya, Maria Laurentia; Ameliana, Yemy; Widjaja, Jennifer (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Pregnancy-related oral health conditions highlight the importance of maintaining dental care, as they can be detrimental to both mother and fetus. In Indonesia, there are considerable gaps in access to general and dental healthcare and there is a lack of reliable data on the oral health status and dental care provision for pregnant women. This study aimed to gain preliminary findings on the oral health status of a vulnerable sample of pregnant women through assessing decay, missing, and fillings (DMFT) at the Made community health centre. In order to secure the health of mothers and children data of this study might improving access to dental care for pregnant women needs to be a priority in relevant policies.